Synthetic Biology and the United Nations. Issue 11 (November 2019) - Lai, Hung-En; Canavan, Caoimhe; Cameron, Loren; Moore, Simon; Danchenko, Monika; Kuiken, Todd; Sekeyová, Zuzana; Freemont, Paul S.
Abstract : Synthetic biology is a rapidly emerging interdisciplinary field of science and engineering that aims to redesign living systems through reprogramming genetic information. The field has catalysed global debate among policymakers and publics. Here we describe how synthetic biology relates to these international deliberations, particularly the Convention on Biological Diversity (CBD).